Could France bring NATO and the EU closer together? Options for the French EU presidency - Ronja Kempin (Stiftung Wissenschaft und Politik (SWP), 2008)
In August 2007 Nicolas Sarkozy announced that he wanted his country to rejoin NATO's integrated military command. The French president believes that if substantial progress is to be made in establishing a capable European Security and Defense Policy (ESDP), France has to become a full member of the alliance once again. Yet as the French EU Presidency approaches, the formula of »rejoining NATO equals more ESDP« seems to have lost its power. It could only work if France were to use its EU Presidency for a masterstroke: connecting NATO and the EU by creating an operational civil-military EU planning and conduct capability closely linked to NATO's capacities at SHAPE. This would be an option with no losers, and one that also could reward France with a central EU leadership position, for example the post of the first »EU foreign minister.«
Keywords: 350